2016
DOI: 10.2298/tsci130204003h
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement with elliptical tube under turbulent flow TiO2-water nanofluid

Abstract: Heat transfer and friction characteristics were numerically investigated, employing elliptical tube to increase the heat transfer rate with a minimum increase of pressure drop. The flow rate of the tube was in a range of Reynolds number between 10000 and 100000. The FLUENT software is used to solve the governing equation of CFD (continuity, momentum, and energy) by means of a finite volume method. The electrical heater is connected around the elliptical tube to apply uniform heat flux (3000 W/m 2) as a boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Some review papers have contained the studies of nanofluid with porpous medium in the heat exchanger Agarwal et al [31], Hussein et al [32]. Hussein et al [33][34][35] have investigated numerically the heat transfer and friction characteristics by employing elliptical tube to increase the heat transfer rate with a minimum increase of pressure drop. It was concluded that the heat transfers and pressure drop increase with increasing volume concentrations but decreasing with diameters of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Some review papers have contained the studies of nanofluid with porpous medium in the heat exchanger Agarwal et al [31], Hussein et al [32]. Hussein et al [33][34][35] have investigated numerically the heat transfer and friction characteristics by employing elliptical tube to increase the heat transfer rate with a minimum increase of pressure drop. It was concluded that the heat transfers and pressure drop increase with increasing volume concentrations but decreasing with diameters of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The heat exchanger tubes (HET) are the core components enriched with various insert geometries to enhance heat transfer rate in most of the mechanical and thermal equipment's used in engineering devices to industrial and house hold appliances [1][2][3]. In the present scenario many studies have been carried out with the aim of energy saving by minimize the size, cost and power consumption of various heat exchanger techniques [4][5][6]. The compact and geometrically enriched heat exchanger with various inserts was found an efficient way to enhance the THERMAL SCIENCE: Year 2019, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulent forced convection heat transfer of water and nanofluid inside tube under single phase approach was carried out by the authors of References [2][3][4][5][6]. Pak and Cho [7] were investigated the effect of two different metallic oxide particles, titanium dioxide and alumina with mean diameters of 27 and 13 nm, respectively on base fluid (water) experimentally.…”
Section: Introductionmentioning
confidence: 99%